2008
DOI: 10.1007/s00213-008-1342-1
|View full text |Cite
|
Sign up to set email alerts
|

Tolcapone enhances food-evoked dopamine efflux and executive memory processes mediated by the rat prefrontal cortex

Abstract: Tolcapone enhanced PFC DA efflux associated with the anticipation and consumption of food when compared to saline controls. Chronic and acute treatment with tolcapone also reduced the number of errors committed during acquisition of the DSWSh. However, no dissociable effects were observed in experiments designed to selectively assay encoding or recall in well-trained animals, as both experiments showed improvement with tolcapone treatment. Taken together, these data suggest a generalized positive influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 59 publications
(65 reference statements)
6
47
0
Order By: Relevance
“…Lapish et al, (2009) found that a 30.0 mg/kg dose of Tolcapone amplified PFC DA efflux by ~100% during anticipation and consumption of a small amount of food, which is comparable to the amount of DA released after treatment with a low dose (0.15 mg/kg) of the DA-releasing agent, AMPH (Berridge and Stalnaker, 2002). The findings with Tolcapone in 2CAP, therefore, prompted the assessment of AMPH in 2CAP to examine if the differential manner that the two drugs target the DA system would yield different behavioral outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lapish et al, (2009) found that a 30.0 mg/kg dose of Tolcapone amplified PFC DA efflux by ~100% during anticipation and consumption of a small amount of food, which is comparable to the amount of DA released after treatment with a low dose (0.15 mg/kg) of the DA-releasing agent, AMPH (Berridge and Stalnaker, 2002). The findings with Tolcapone in 2CAP, therefore, prompted the assessment of AMPH in 2CAP to examine if the differential manner that the two drugs target the DA system would yield different behavioral outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, COMT inhibitors enhance extracellular PFC DA levels (Tunbridge et al, 2004; Lapish et al, 2009) and DA content in the hippocampus with minimal effects on striatal DA (Huotari et al, 1999; Laatikainen et al, 2013). This is likely due to different reuptake mechanisms in cortex and striatum (Mazei et al, 2002; Käenmäki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lower rates of PFC DA catabolisis following neurotransmitter release, due to a lower COMT activity, increases the overflow of synaptic DA into the extrasynaptic space where it can stimulate extrasynaptic D1-receptors, thereby stabilizing cognitive performance (Garris et al, 1993;Tunbridge et al, 2004;Winterer and Weinberger, 2004;Lapish et al, 2009). In addition, as discussed, this increase in tonic PFC activity may also dynamically increase tonic DA output in the amygdala, which in turn sensitizes emotional processing in response to stressful or aversive cues (Smolka et al, 2005;Drabant et al, 2006;Heinz and Smolka, 2006;Hashimoto et al, 2007;Smolka et al, 2007;Williams et al, 2010).…”
Section: Da Metabolization (Catechol-o-methyltransferase)mentioning
confidence: 98%
“…Furthermore, the subsequent metabolism of L-DOPA by COMT clearly limits its availability in the brain. The two COMT inhibitors E and T, approved as adjuncts in the therapy of PD, increase the availability of L-DOPA for conversion to dopamine in the brain (25) mainly by preventing the extensive metabolism of L-DOPA through O-methylation in the periphery (E and T) and partly in brain (T) (77). However, the potential for the use of T as neuroprotective drug in AD or PD is limited due to the fact that it has been shown to cause severe hepatotoxicity resulting in its withdrawal from the market in many countries leaving entacapone as the only COMT inhibitor presently available in the clinic for the treatment of PD (78).…”
Section: Discussionmentioning
confidence: 99%